The Culture of Strengths Makes Them Feel Valued and Competent: Aboriginal Children, Child Welfare, and a School Strengths Intervention - Brownlee, Keith; Rawana, Edward; MacArthur, Julia; Probizanski, Michelle (First Peoples Child & Family Review, 2010)
Schools are an important community partner in providing structural supports and wrap around services for children involved with the child welfare system. In this paper, we discuss the implementation of a culturally sensitive strengths-based intervention approach within an elementary school and its value to Aboriginal children. This article discusses the theoretical foundation of the strengths intervention approach and provides a description of a strength assessment tool as well as the implementation of the intervention with specific relevance to Aboriginal students involved with the child welfare system. Two case studies are presented, which illustrate the value of the strengths approach for individual students.